Measures to Increase Recoveries and Avoid Concentrate Disposal: Principles to Control Scaling and Reduce Concentrate Disposal in Reverse Osmosis Applications - Pervov, Alexei (Journal of Membrane and Separation Technology, 2014)
The present work is aimed at development of a new approach to reduce RO concentrate flow and to increase recovery. The described techniques enable us to remove calcium carbonate from RO concentrate by means of "seed" сrystallization. These proposed techniques use "open channel" spiral wound membrane modules that can directly treat water with high scaling and fouling potentials without pretreatment. The experimental procedure is described and experimental plots are presented that describe precipitation kinetics. The test membrane unit was operated in circulation mode and recovery values reach 95% or higher. RO concentrate constantly passed through the precipitation reactor where seed crystals were contained. Seed crystal formation was initiated by injecting caustic solution to RO concentrate. The driving force for crystal growth was constantly created by RO process due to increase of calcium and carbonate ion concentration values. Fouling control is achieved by providing sufficient cross flow velocities, flushings and cleanings. Coagulated suspended matter after membrane flushes is collected, sedimented and finally dewatered. The concentrated solution that contains rejected salts and impurities constitutes no more than 1 per cent of initial feed water volume and can be withdrawn together with wet sludge as a sludge moisture. The described technical procedure enables us to completely utilize concentrate and produce quality product water, softened water and sludge.